Application of the Problem Based Learning Model to Improve Critical Thinking Skills for Grade IV Elementary School Students - Rahmawati, Elyana (Universitas Sebelas Maret, 2020)
This study aims to improve critical thinking skills through the application of a Problem Based Learning based. This research is a classroom action research conducted in two cycles with planning, implementation, observation, and reflection stages. Data collection instruments use question instruments, observation sheets, documentation, and field notes. The subject of the study was the fourth grade students of SDN 1 Muryolobo. The results showed an increase in critical thinking skills as indicated by the data in the pre cycle of 42%, in the first cycle increased by 67,23%, and in the second cycle increased by 80,72%. Increasing critical thinking skills also affects the students learning outcomes. This is indicated by the learning outcomes on Indonesian language in pre cycle, cycle I, and cycle II, are 45%, 68%, and 81%. Furthermore, the learning outcomes of IPS in pre cycle, cycle I, and cycle II are 36%, 63%, and 81%.